Fibrosis is not just fibrosis – basement membrane modelling and collagen metabolism differs between hepatitis B‐ and C‐induced injury. Issue 11 (3rd October 2016) - Nielsen, M. J.; Karsdal, M. A.; Kazankov, K.; Grønbæk, H.; Krag, A.; Leeming, D. J.; Schuppan, D.; George, J.
Summary: Background: While morphological patterns differ, the molecular phenotype of liver fibrosis is considered a stereotypical response to chronic liver injury. However, with different cellular triggers and networks regulating fibrosis, the molecular responses of the injured liver may not be identical. Aim: To investigate whether differences in extracellular matrix (ECM) composition of the liver during fibrogenesis in two seemingly similar types of viral hepatitis could be reflected by differences in ECM turnover. Methods: Utilising a cross‐sectional design, we measured specific ECM protein fragments in plasma from 197 chronic hepatitis B (CHB) patients and 403 chronic hepatitis C (CHC) patients matched for inflammation grade and fibrosis stage. Markers of matrix metalloprotease degraded type I, III, IV and VI collagen (C1M, C3M, C4M, C6M) and type III and IV collagen formation (Pro‐C3, P4NP7S). Results: P4NP7S, C3M, C4M and C6M were significantly elevated in CHB compared to CHC. In contrast, Pro‐C3 was significantly elevated in CHC compared to CHB. Pro‐C3, C3M and C4M were increased in parallel with inflammation and fibrosis in both cohorts. C6M and P4NP7S were associated with inflammation and fibrosis only in CHC. Basement membrane collagen fragments P4NP7S and C4M were significantly higher in matched activity and fibrosis cohorts within CHB vs CHC. Conclusion: The main parameters to determine extracellular matrix biomarker levels are inflammation, fibrosis, and type of viral insult. Compared to CHC, CHB appears to induce a higher basement membrane turnover. This suggests that there are aetiology‐dependent molecular signatures in liver fibrosis that could have pathogenic and diagnostic implications.